Tumoural form of Whipple's disease simulating carcinomatosis - Costa,Jamille Hemétrio Salles Martins (2014)
Whipple's disease is a rare disease caused by the actinomycete bacteria Tropheryma whipplei, which cause intestinal infection. The most common symptoms are chronic diarrhoea, weight loss, abdominal pain, arthritis and neurological abnormalities, which can be fatal. This paper reports a case of a 57-year-old Brazilian woman with diarrhoea, vomiting, abdominal pain, appetite loss, intermittent fever, malaise, weight loss and malnutrition. Migratory polyarthralgia and recurrent visual scotomas preceded the symptoms. The retroperitoneal pseudotumour formation finding was associated with prolonged wasting syndrome, which did not respond to usual therapies, thus leading to the investigation of carcinomatosis disease. After laparotomy, biopsy and histochemical study of the lesions with negative results for malignancy, we proceeded to the investigation of Whipple's disease, which was then confirmed. The patient improved clinically and started gaining weight after using ceftriaxone (IV).